2016
DOI: 10.19044/esj.2016.v12n15p263
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Strategic Information Systems Implementation In Government Parastatals: A Case Of Kenya Forest Service, Mau Forest Conservancy

Abstract: The operations of parastatals could be greatly enhanced by the wellfocused application of information systems to support improvements in productivity, management effectiveness and ultimately, the quality of services offered to citizens. Assessing the strategies of information systems (ISs) implementation has been identified as one of the most critical issues in IS field. However, studies relating to this issue within the context of kenyan parastatals are few and lack the ability to propose a major set of facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 10 publications
0
0
0
Order By: Relevance
“…In the studies contacted by Koech and Were (2016) on the factors influencing strategy implementation at the National Treasury-Kenya. The study concluded that organizational culture and organizational structure have a direct influence on strategy implementation.…”
Section: Critique Of Existing Literature Relevant To the Studymentioning
confidence: 99%
See 2 more Smart Citations
“…In the studies contacted by Koech and Were (2016) on the factors influencing strategy implementation at the National Treasury-Kenya. The study concluded that organizational culture and organizational structure have a direct influence on strategy implementation.…”
Section: Critique Of Existing Literature Relevant To the Studymentioning
confidence: 99%
“…The content analysis regarding the papers in the literature review provides detailed overview of main issues covered by the research on influence of organization culture on strategy implementation and has enabled the identification of principal research gap on the topic. From the literature review its apparent that several scholars have established that is positive and significance influence of organization culture on strategy implementation (Cheruiyot, Kihara & Senaji, 2018;Koech & Were ,2016;Tele & Gachunga, 2019). In contrast, (Ngigi & Namusonge, 2019;Mohamed & Olweny, 2019;Akuei, Katuse & Njenga, 2016;Kagumu & Njuguna, 2016;Isaboke, 2015;Kinyua, Njoroge, Wanyoike & Kiiru, 2015) indicates that some studies contended that it is very difficult to examine the relationship between organization culture and implementation of strategies, there was devoid of empirical studies and theories, how organization culture constructs were measured for the utilization of inferential statistics and conceptualization of organizational culture as compared to the study which has conceptualized organizational culture in terms of values and beliefs.…”
Section: Knowledge Gapmentioning
confidence: 99%
See 1 more Smart Citation
“…Making the plan happen is as critical as the actual execution that leads to results. In addition, all organization members should know why the plan was developed, what it means to the organisation, who will be involved in its implementation and how they can contribute to the organisation's success (Koech & Were, 2016). Stakeholder analysis helps an organisation to identify interests of all stakeholders who may affect or be affected by a project.…”
Section: Introductionmentioning
confidence: 99%
“…The mix of strategic management practices adopted by organizations vary and lend themselves to the influence of what decision makers in the firm believe the definition of strategy imply and the domains that should be addressed. To illustrate, Branislav (2014) noted that such domains include the formulation, implementation and evaluation of cross-functional decisions while Koech and Were (2016) asserted that strategic practices should emphasize such domains as formation of strategy, goal-setting, implementation, monitoring and analysis. Small and medium scale enterprises (SMEs) play a crucial role in their economies; however, a sustained observation is that their survival and sustainability are threatened by the competitive and turbulent nature of the environment they have to operate in (Sandada, 2015).…”
mentioning
confidence: 99%